The struggles of small and medium enterprises in Malaysia: navigating economic uncertainty - Saidi, Normaizatul Akma; Ahmad Raston, Nursalihah; Mohd Radzi, Naziatul Aziah; Saidi, Noraida (Universiti Teknologi MARA, Terengganu, 2024)
The Malaysian economy is primarily composed of small and medium-sized firms, or SMEs. Nearly 70% of workers are employed by small enterprises, which account for 98.5% of all businesses in Malaysia (Department of Statistics, 2021). The GDP of Malaysia was boosted by 1,226,494 small enterprises in 2021, amounting to RM500 billion, or almost 38%. Even though SMEs are the backbone of the country’s economy, they frequently encounter difficulties, ranging from volatile international markets to modifications in internal policies. This article highlighting their challenges for building resilience in the current economic situation.